Sistem Informasi Pelayanan Rekam Medis Puskesmas Purowoyoso Berbasis Web - Hidayat, Taufik; Suhari, Yohanes; Mariana, Novita (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Purwoyoso Health Center, located at Jl. Siliwangi No. 572, is a non-inpatient health facility that provides medical record and laboratory examination services. Currently, the patient data recording and search system is still done manually, resulting in difficulties in finding patient data who do not bring a medical book (KIB), as well as increasing the risk of data duplication and loss. To overcome this problem, the development of a web-based medical record service application is proposed as an effective solution, by following the waterfall method and using tools such as DFD, flowchart, and MySQL database. Application testing will be carried out using the black box method to ensure its functionality. The advantages of this application include increased efficiency of service time, ease of searching for patient data, and better data storage security. With the implementation of this application, it is hoped that Purwoyoso Health Center can improve the quality of medical record services and provide faster and more accurate access to patient information, as well as support better decision-making in health services.